Jung's views on causes and treatments of schizophrenia in light of current trends in cognitive neuroscience and psychotherapy research II: Psychological research and treatment - Silverstein, Steven M. (Journal of analytical psychology, 2014)
Jung was the first to emphasize the importance of psychological factors in the aetiology and treatment of schizophrenia. Despite this, and other seminal contributions, his work on schizophrenia is almost completely ignored or forgotten today. This paper, a follow-up to one on Jung's theories of aetiology and symptom formation in schizophrenia (Journal of Analytical Psychology, 59, 1) reviews Jung's views on psychological approaches to research on, and treatment of, the disorder. Five themes are covered: 1) experimental psychopathology; 2) attentional disturbance; 3) psychological treatment; 4) the relationship between the environment (including the psychiatric hospital) and symptom expression; and 5) heterogeneity and the schizophrenia spectrum. Review of these areas reveal that Jung's ideas about the kind of research that can elucidate psychological mechanisms in schizophrenia, and the importance of psychotherapy for people with this condition, are very much in line with contemporary paradigms. Moreover, further exploration of several points of convergence could lead to advances in both of these fields, as well as within analytical psychology.